2016
DOI: 10.1002/lary.26329
|View full text |Cite
|
Sign up to set email alerts
|

Disease Characteristics and Electromyographic Findings of Nonsurgery-Related Unilateral Vocal Fold Paralysis

Abstract: 4. Laryngoscope, 127:1381-1387, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Husain et al showed that the time course of vocal recovery in IVFP follows a different pattern than that of iatrogenic vocal fold paralysis, with higher rates of recovery in the first 5 months in IVFP. Laryngeal electromyographic studies have shown that patients with IVFP have less severe denervation than those with vocal fold paralysis of known causes . Taken together, these data suggest that the pathophysiology of IVFP may be distinct from that of typical iatrogenic vocal fold paralysis.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Husain et al showed that the time course of vocal recovery in IVFP follows a different pattern than that of iatrogenic vocal fold paralysis, with higher rates of recovery in the first 5 months in IVFP. Laryngeal electromyographic studies have shown that patients with IVFP have less severe denervation than those with vocal fold paralysis of known causes . Taken together, these data suggest that the pathophysiology of IVFP may be distinct from that of typical iatrogenic vocal fold paralysis.…”
Section: Introductionmentioning
confidence: 85%
“…This difference (53% vs. 22%) is probably more impressive than it seems because surgeries with known risk to both nerves accounted for 54 of the 107 patients, so the simultaneous RLN/SLN deficits were largely explainable in the iatrogenic group. To account for the large proportion of IVFP patients with simultaneous RLN/SLN deficits, Pei et al hypothesized that many cases of IVFP may be caused by neuritis involving the segment of the vagus nerve proximal to the takeoff point of the superior laryngeal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenic immobility can be caused by a disease process of any part of the vagus nerve from its origin in the medullary nucleus ambiguous or its supranuclear tracts in the brain, to the recurrent laryngeal nerve. 13 22 Brain tumors, from brainstem to jugular foramen, strokes, and demyelinating diseases are rarer etiologies. Recurrent laryngeal nerve paralysis can be also caused by non-neoplastic space-occupying lesions including aortic aneurysm, mitral stenosis, and mediastinal cysts.…”
Section: Possible Causes Of London’s Vocal Paralysismentioning
confidence: 99%
“…Systemic causes of recurrent laryngeal paralysis include lead poisoning, bacterial infections (such as diphtheria), or viral illness. More than 85% of UVCP 13 22 has three main causes: (1) nerve injury during surgery (of thyroid or mediastinum), (2) neoplastic invasion along the path of the recurrent laryngeal nerve, and (3) an inflammatory process usually due to a viral infection.…”
Section: Possible Causes Of London’s Vocal Paralysismentioning
confidence: 99%
See 1 more Smart Citation